Ballistic Mechanism of Adatom Aggregation during Initial Stages of Thin Film Formation - Kanapickas, A. (Elektronika ir Elektrotechnika, 1997)
The mechanism of thin film formation based on the ballistic aggregation of impinged atoms with clusters is proposed. The experimental results are analyzed and it is shown that introduced mechanism prevails in the cluster growth when the energies of arriving atoms significantly exceeds adsorption energy. Theoretical value of the length of the ballistic trajectory is obtained equal to 20 nm. It is shown that the electronic stopping is responsible for the loss of kinetic energy of ballistic atoms on atomically flat substrate. The kinetics of thin film growth at the early stage of deposition is analyzed using phenomenological model based on the system of clustering equation with size dependent aggregation of ballistic atoms and good agreement between calculated cluster size distributions and experimental results is obtained.